Association between breastfeeding and overweight in preschoolers. - da Costa Macêdo, Rivaldo; Viana Ramos, Carmen; de Azevedo Paiva, Adriana; do Carmo de Carvalho e. Martins, Maria; Pinheiro Landim Almeida, Camila Aparecida; Rebêlo Sampaio da Paz, Suzana Maria (Acta Paulista de Enfermagem, 2020)
Objective: To analyze association between breastfeeding and overweight in preschoolers. Methods: A cross-sectional study with 448 preschoolers from 10 Municipal Centers of Early Childhood Education in the city of Teresina, state of Piauí. A meeting was held with the parents, at which time the structured questionnaire with questions related to sociodemographic data and past feeding of the children was applied. Subsequently, the anthropometric measurements of the children (weight and height). Overweight overweight + obesity) was considered when the z-score result was greater than or equal to +2. Children younger than +2 were classified as not overweight. The association between exclusive breastfeeding up to six months, exclusive breastfeeding up to four months and breastfeeding with the child's nutritional status was analyzed using Pearson's chi-square test (c²), while the prevalence ratio (PR) was estimated to quantify the associations between breastfeeding and nutritional status controlled by sociodemographic variables. All estimates and 95% confidence intervals were calculated using the robust variance Poisson regression model. Results: The prevalence of overweight and the proportion of children who received exclusive breastfeeding until 6 months of age were 11.16% and 41.9%, respectively. Overweight was 2.5 times higher among nonbreastfed children (95% CI: 1.09; 5.83). After controlling for sociodemographic variables, it was found that children older than 48 months were at high risk for overweight (PR: 1.69; 95% CI: 1.01; 2.85) compared to children younger than 48 months. months old (p = 0.04). Conclusion: The present study demonstrated that breastfed newborns were protected against overweight.